Development of vocational learning and training methods (case study: Bandung vocational and productivity training center) - Tri Bagus Aji Pamungkas; Ryan Ilham Syahputra; Muhammad Taufik; Islah Shalahuddin; Iu Rusliana (Jurnal Ekonomi, 2024)
The aim of this research is to determine the development of vocational learning and training methods at the Bandung Vocational and Productivity Training Center, Ministry of Manpower of the Republic of Indonesia. The research method used is a descriptive analysis approach. Where data and information collection were carried out using observation techniques, interviews and Focus Group Discussion (FGD) which lasted for two hours structural and functional officials (Instructors) at the Bandung Vocational and Productivity Training Center. The results of the research show that the development of learning and training methods went well and was very satisfactory through several stages, namely, carried out by using training needs analysis through TNA (Training Need Analysis) which was obtained from industry needs, then carried out Vocational Training Program Development Planning, Implementation of the Training Program, and finally, Training Evaluation is carried out both through Written Tests and Practical Tests. From the results of this research, it is hoped that in the future facilities and infrastructure can be improved to support the implementation of vocational training that produces superior and competitive human resources.